Conversations about children when an important adult is at end of life: an audit - Hanna, JR; Rapa, E; Miller, M; Turner, M; Dalton, LJ (SAGE Publications, 2021)
Purpose: Health and social care professionals report it challenging to have conversations with families when an important adult in the life of a child is at end of life, often feeling this aspect of care is the responsibility of other colleagues. This study aimed to understand professionals’ perceived role in family-centered conversations as part of routine care at end of life, and how to promote this element of care in clinical practice.